Early initiation of peritoneal dialysis improves postoperative recovery in children with right ventricular outflow tract obstructive lesions at high risk of fluid overload: a propensity score-matched analysis. (9th March 2018) - Pan, Tuo; Li, Dan; Li, Shoujun; Yan, Jun; Wang, Xu
Abstract: OBJECTIVES: Postoperative fluid overload is common in children after cardiac surgery, especially for those with right ventricular outflow tract obstruction, which is associated with poor outcomes. This study was conducted to investigate whether early peritoneal dialysis (PD) was associated with improved outcomes in these children at high risk of fluid overload. METHODS: Between January 2010 and January 2015, a total of 2555 consecutive patients with right ventricular outflow tract obstruction underwent anatomical repair. Using empirical risk evaluation, 219 patients at high risk of fluid overload were identified. A propensity score matching was performed to correct the selection bias and identify the comparable patient groups: the early PD group, in whom PD was initiated within 6 h of admission in paediatric ICU, and the control group, without early PD. The mechanical ventilation time, vasoactive-inotropic score and time to negative fluid balance were compared in 45 matched patient pairs (totally 90). RESULTS: After propensity matching, there were no statistically significant differences between the 2 groups in terms of demographics and preoperative characteristics. The early PD group had shorter mechanical ventilation time [median 49 h, interquartile range (IQR) 31–97 h vs median 76 h, IQR 55–166 h; P  < 0.01]; lower vasoactive-inotropic score (median 17, IQR 16–21 vs median 22, IQR 18–26; P  < 0.01); shorter duration of inotrope requirement (median 7 days, IQR 6–9 days vs median 8 days, IQR 7–13 days; P  < 0.01); shorter time to negative fluid balance (median 20 h, IQR 13–34 h, vs median 48 h, IQR 40–74 h; P  < 0.01) and a higher rate of negative fluid balance at 24 h (69% vs 29%, P  < 0.01). CONCLUSIONS: When compared with the control group, the early PD group showed shorter mechanical ventilation time, less inotropic requirement and lower time to attain negative fluid balance. On the basis of our empirical risk-evaluation practice, early PD could improve immediate postoperative recovery in children with right ventricular outflow tract obstruction.